Ta‘līm al-Lugah al-‘Arabiyyah ‘ala Asasi al-Madkhali al-Ittiṣali Khilāli Ja’iḥah Covid fī Madrasah al-Ma’arif Singosari Malang / Learning Arabic Based on Communicative Approach During the Covid Pandemic in MA Al-Ma'arif Singosari Malang - Anita Andriya Ningsih; Muhammad Mubasysyir Munir (Jurusan Pendidikan Bahasa Arab UIN Sunan Kalijaga, 2022)
This study describes learning Arabic based on a communicative approach during the covid pandemic in four language skills and the obstacles faced in implementing a communicative strategy in learning Arabic. By using the research method used is the descriptive qualitative method with data collection through interviews and observation. The results of this study show that first, Arabic learning activities with a communicative approach can be implemented in four language skills by forming activities that refer to the teacher's principle only as a facilitator to provide direction and guidance to students to be more active during the learning process. Second, the obstacles in its implementation are the lack of quality of students' confidence in speaking skills, difficulty in finding materials that suit students' interests, and taking a long time to implement. Keywords: Language Skills, Communicative Approach, Barriers to the Learning Process Abstrak Penelitian ini bertujuan untuk mendeskripsikan pembelajaran Bahasa Arab berbasis pendekatan komunikatif pada masa pandemic covid dalam empat ketrampilan berbahasa serta hambatan yang dihadapi dalam mengimplementasikan pendekatan komunikatif dalam pembelajaran Bahasa Arab. Dengan menggunakan metode penelitian yang digunakan adalah metode deskriptif kualitatif dengan pengumpulan data melalui wawancara dan observasi. Hasil penelitian ini menunjukkan pertama, aktivitas pembelajaran bahasa arab dengan pendekatan komunikatif dapat diimplementasikan pada empat ketrampilan Bahasa dengan membentuk kegiatan yang mengacu pada asas guru hanya sebagai fasilitator guna memberikan pengarahan dan pembimbingan kepada siswa agar lebih aktif selama proses pembelajaran. Kedua, hambatan dalam pengimplementasiannya adalah kurangnya kualitas percaya diri siswa dalam keterampilan berbicara, kesulitan dalam mencari materi yang sesuai minat siswa, dan membutuhkan waktu yang cukup lama dalam penerapannya. Kata Kunci: Keterampilan Berbahasa, Pendekatan Komunikatif, Hambatan Proses Pembelajaran